O conselho tutelar de Macapá como alternativa para ações de educação comunitária - Nogueira, Ricardo Soares (2009)
The actuality from the Advice Custody well into Macapá approached from the of the examples collected well into appointments with the advisers and the one basal of this situation in an attempt to account for the anthropologies philosophic than it is to this one actual , they are he presents in this I work stretching from the starts from the art as of bring up , having the one Europe as a reference , as far as our conquest and challenges , passing to it consciousness of what no body he educates nobody and that that's why , the advice Custody can be a nice proposal as a environmental about to education community at its felt lato sensu as far as the socialization of the Advice Custody at the Brazil and the situation from that Macapá. Keywords: Education, Comunication and Children.